Local fiscal autonomy in Toronto - Slack, Enid (Anuario de Derecho Municipal, 2023)
Local fiscal autonomy depends on the extent to which local governments rely on their own source revenues rather than intergovernmental transfers and also on their ability to set their own tax rates. Compared to other major cities around the world, Toronto appears to have a lot of local autonomy because it is less dependent on intergovernmental transfers and more reliant on property taxes and user fees. Nevertheless, its autonomy is limited by provincial government restrictions on how these taxes and fees are levied and also by the conditions imposed on federal and provincial transfers. Toronto also has fewer revenue-raising options than many other cities. This paper describes the extent to which Toronto enjoys fiscal autonomy and evaluates the degree to which it takes advantage of the autonomy it has in setting tax rates and making other financial decisions. The paper considers some of the fiscal challenges the city now faces and some future challenges on the road ahead. It evaluates the extent to which the city can respond to these various external shocks with the resources at its disposal. It concludes that, although Toronto enjoys some local fiscal autonomy, it would benefit from having more diversified revenue sources. This paper describes the extent to which Toronto enjoys fiscal autonomy and evaluates the degree to which it takes advantage of the autonomy it has in setting tax rates and making other financial decisions. The paper considers some of the fiscal challenges the city now faces and some future challenges on the road ahead. It evaluates the extent to which the city can respond to these various external shocks with the resources at its disposal. It concludes that, although Toronto enjoys some local fiscal autonomy, it would benefit from having more diversified revenue sources.